Investigating the determinants of firm performance: A qualitative comparative analysis of insurance companies - Stavros Kourtzidis; Nickolaos G. Tzeremes (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this paper is to use tenets of the complexity theory in order to study the effect of various determinants of firm's performance, such as CEO's compensation and age, for the case of 72 insurance companies. Design/methodology/approach The authors identify the asymmetries in the data set by creating quantiles and using contrarian analysis. Instead of ignoring this information and use a main effects approach, all the available information in the data set is taken into account. For this purpose, the authors use qualitative comparative analysis to find alternative equifinal routes toward high firm performance. Findings Five configurations are found which lead to high performance. Every one of the five configurations is found to be sufficient but not necessary for high firm performance. Originality/value The research findings contribute to a better understanding of the determinants of firm's performance taking into account the asymmetries in the data set. The authors identify alternative paths toward high firm performance, which could be vital information for the decision maker inside a firm.
Keywords: 650; Complexity theory; Qualitative comparative analysis; Contrarian analysis; Insurance companies; Compensation